2004
DOI: 10.1042/cs20030165
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin response after correction of severe hypoxaemia due to acute respiratory failure in chronic obstructive pulmonary disease patients

Abstract: In order to determine the initial values and dynamic changes of EPO (erythropoietin) after therapy, 57 consecutively presenting, typical COPD (chronic obstructive pulmonary disease) patients with chronic hypoxia and acute exacerbated serum EPO levels were serially measured. Initial mean EPO levels were slightly above the normal range (41.4 +/- 83.5 units/l), but in the majority of patients the initial EPO levels were significantly reduced. Following the correction of hypoxaemia, mean EPO levels decreased to 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In keeping with this observation, a previous paper in patients with a number of causes of acute respiratory failure, including COPD, pneumonia and heart failure, also reported reduced Epo plasma levels [31]. We propose here that Epo down-regulation during ECOPD can be explained by the burst of inflammation that occurs during these clinical circumstances [32], as shown here by a significant increase in leukocyte and neutrophil counts, as well as by the raised concentration of hsC-RP during ECOPD (table 5).…”
Section: Discussionmentioning
confidence: 52%
“…In keeping with this observation, a previous paper in patients with a number of causes of acute respiratory failure, including COPD, pneumonia and heart failure, also reported reduced Epo plasma levels [31]. We propose here that Epo down-regulation during ECOPD can be explained by the burst of inflammation that occurs during these clinical circumstances [32], as shown here by a significant increase in leukocyte and neutrophil counts, as well as by the raised concentration of hsC-RP during ECOPD (table 5).…”
Section: Discussionmentioning
confidence: 52%
“…Following correction of hypoxemia, EPO significantly decreased, but not all patients showed the same pattern; in those with lower initial EPO levels and erythrocyte count, EPO levels significantly increased [81]. In another longitudinal study of 132 severe COPD patients using LTOT who were followed for 3 years, Hb levels decreased significantly among polycythemic patients, but effects in anaemic patients were smaller [82].…”
Section: Oxygen Supplementationmentioning
confidence: 88%
“…Against this background, Pavlisa et al [81] studied the impact of hypoxemia correction in 57 COPD patients with chronic hypoxemia during AECOPD. Following correction of hypoxemia, EPO significantly decreased, but not all patients showed the same pattern; in those with lower initial EPO levels and erythrocyte count, EPO levels significantly increased [81].…”
Section: Oxygen Supplementationmentioning
confidence: 99%
“…[20] However, in some other studies, it has been shown that aging is responsible for the greater prevalence of anemia in COPD patients. [17,18,21,22] Even in our study, the maximum male anemic patients were in the age group of 71-80 years (10.6%) followed by 81-90 years (6.3%). However, in the female anemic patients, the trend was slightly different.…”
Section: Discussionmentioning
confidence: 92%